2019
DOI: 10.1111/ane.13113
|View full text |Cite
|
Sign up to set email alerts
|

Use of coping strategies in MND/ALS: Association with demographic and disease‐related characteristics

Abstract: Objective: Understanding the use of coping strategies and which factors are associated with strategy utilization might help clinical staff anticipate which coping strategies individuals are more likely to utilize. In this study, we assess coping strategy use in the motor neuron disease (MND, also known as amyotrophic lateral sclerosis [ALS]) population and examine associations of demographic and disease variables with individual coping strategies. Participants and Methods:A total of 233 participants with MND/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Three studies reported significant associations between sex and some coping strategy subscales. Female sex was found to be related with greater use of social support coping strategies, such as emotional support , seeking instrumental social support (Schluter et al, 2019), seeking emotional social support (Schluter et al, 2019), focus and venting of emotions (Schluter et al, 2019). Furthermore, Schluter et al ( 2019)'s study found that female sex was associated with a higher use of restraint and behavioural and mental disengagement (Table 3).…”
Section: Demographic Factors Associated With Coping Strategiesmentioning
confidence: 96%
See 4 more Smart Citations
“…Three studies reported significant associations between sex and some coping strategy subscales. Female sex was found to be related with greater use of social support coping strategies, such as emotional support , seeking instrumental social support (Schluter et al, 2019), seeking emotional social support (Schluter et al, 2019), focus and venting of emotions (Schluter et al, 2019). Furthermore, Schluter et al ( 2019)'s study found that female sex was associated with a higher use of restraint and behavioural and mental disengagement (Table 3).…”
Section: Demographic Factors Associated With Coping Strategiesmentioning
confidence: 96%
“…Additionally, younger age was related to more emotion-focused coping (e.g., positive thought (Tramonti et al, 2012) and positive reframing ) and social support coping (e.g., emotional support , venting Schluter et al, 2019)).…”
Section: Demographic Factors Associated With Coping Strategiesmentioning
confidence: 96%
See 3 more Smart Citations